A Randomized Controlled Trial Assessing the Effect of a Continuous Subcutaneous Infusion of Local Anesthetic Following Elective Surgery to the Great Toe. Issue 2 (April 2017) - Rose, Barry; Kunasingam, Kumar; Barton, Tristan; Walsh, James; Fogarty, Karen; Wines, Andrew
Local anesthetic use for wound infusions, single injection, and continuous nerve blocks for postoperative analgesia is well established. No study has investigated the effect of a continuous block of the saphenous and superficial peroneal nerves at the level of the ankle joint following first ray surgery. A double blind randomized controlled trial was designed. One hundred patients with hallux valgus and rigidus requiring surgical correction were recruited and randomized to receive a postoperative continuous infusion at the ankle of normal saline or ropivacaine for 24 hours. Pain scores were recorded on postoperative days 1 and 7. There were more females than males. Follow-up was 100%. There were no significant differences in demographic data between the 2 randomized groups. There was no significant difference between the absolute visual analog scale scores on day 1 (P = .14) and day 7 (P = .16); nor was there a significant difference in reduction in scores between days 1 and 7 (P = .70). This study has shown no benefit to postoperative analgesia with the use of a continuous infusion of ropivacaine at the ankle. We, therefore, cannot currently recommend its use in the way described. Further studies may still identify a role for continuous local anesthetic infusions at the ankle to improve postoperative analgesia. Levels of Evidence: Level I : Prospective randomised control trial.